Mechanical Behavior of Biodegradable PHB-TPS Reinforced With Oat and Corn Cob Fibers After Accelerated Thermal-Humidity Exposure - Natalia Gomez-Gast; Andrea Guevara-Morales; Ulises Figueroa-López; Eduardo San Martin-Martínez; Horacio Vieyra (International Journal of Polymer Science)
Plant fibers have gained notoriety for reinforcing composite polymers due to their abundance, availability, versatility, and friendliness to the environment. Research in composites of biodegradable polymers with natural fibers as reinforcement will continue because the mechanical and physical properties, processability, and cost of plastics derived from petroleum are still needed in biodegradable polymers. This study analyzed the mechanical stability of biodegradable polyhydroxybutyrate–thermoplastic starch (PHB-TPS) composites reinforced with oat and corn cob fibers under environmental conditions. We investigated how different fiber concentrations affect the mechanical properties of injection-molded composites, aiming to improve PHB’s performance while preserving its biodegradability. The composites were subjected to accelerated temperature/humidity exposure using a climatic chamber to simulate and evaluate mechanical properties before and after long-term environmental exposure to humidity, heat, and cold. Results showed that the exposure in the climatic chamber led to yield strength decreases of up to 80% due to moisture absorption and microcracks at the fiber-matrix interface. The PHB/TPS/oat and cob fiber blends demonstrated mechanical properties comparable to those of FEP (fluorinated ethylene propylene), polyvinylidene chloride (PVDC), and thermoplastic polyolefin (TPO), making them suitable for applications like packaging and containers.